Relationship Between Mitochondrial Biological Function and Breast Cancer: An Approach Based on Mendelian Randomization Analysis. - Miao, Shichen; Ni, Qichao; Fang, Jun; Hashmi, Atif Ali (Breast Journal, 2024)
Objective: This study aims to investigate the potential causal link between mitochondrial function and breast cancer using the Mendelian randomization (MR) analysis. Methods: The data used for this study were obtained from genomewide association studies (GWAS) databases on mitochondrial biological function and breast cancer. Mitochondrial function was considered the exposure variable, breast cancer the outcome variable, and specific single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs). Two MR methods, inverse variance weighting (IVW) and MR‐Egger regression, were used to assess the causal association between mitochondrial function and breast cancer. Data analysis and visualization were performed using R software. Results: The results of the analysis revealed that several genes, including 39S ribosomal protein L34, pyruvate carboxylase, rRNA methyltransferase 3, and cytochrome c oxidase assembly factor 3 homolog, are causally linked to an increased risk of breast cancer in European populations. In addition, cytochrome c oxidase subunit 8A and ADP‐ribose pyrophosphatase were found to be protective factors against breast cancer in European populations. In East Asian populations, 39S ribosomal protein L52, ATP synthase subunit beta, and pyruvate dehydrogenase (acetyl‐transferring) were identified as causal risk factors for breast cancer. Conversely, 39S ribosomal protein L32, ADP‐ribose pyrophosphatase, and cytochrome c oxidase subunit 8A were identified as protective factors against breast cancer in this population. Conclusion: In conclusion, this study provides evidence of a causal relationship between mitochondrial function and breast cancer in both European and East Asian populations. Additional research is warranted to further elucidate the mechanisms underlying this association.